Analysis of Cellular Factors That Mediate Nuclear Export of RNAs Bearing the Mason-Pfizer Monkey Virus Constitutive Transport Element - Kang, Yibin (American Society for Microbiology, 2000)
There is now convincing evidence that the human Tap protein plays a critical role in mediating the nuclear export of mRNAs that contain the Mason-Pfizer monkey virus constitutive transport element (CTE) and significant evidence that Tap also participates in global poly(A)(+) RNA export. Previously, we had mapped carboxy-terminal sequences in Tap that serve as an essential nucleocytoplasmic shuttling domain, while others had defined an overlapping Tap sequence that can bind to the FG repeat domains of certain nucleoporins. Here, we demonstrate that these two biological activities are functionally correlated. Specifically, mutations in Tap that block nucleoporin binding also block both nucleocytoplasmic shuttling and the Tap-dependent nuclear export of CTE-containing RNAs. In contrast, mutations that do not inhibit nucleoporin binding also fail to affect Tap shuttling. Together, these data indicate that Tap belongs to a novel class of RNA export factors that can target bound RNA molecules directly to the nuclear pore without the assistance of an importin β-like cofactor. In addition to nucleoporins, Tap has also been proposed to interact with a cellular cofactor termed p15. Although we were able to confirm that Tap can indeed bind p15 specifically both in vivo and in vitro, a mutation in Tap that blocked p15 binding only modestly inhibited CTE-dependent nuclear RNA export. However, p15 did significantly enhance the affinity of Tap for the CTE in vitro and readily formed a ternary complex with Tap on the CTE. This result suggests that p15 may play a significant role in the recruitment of the Tap nuclear export factor to target RNA molecules in vivo.